The impact of recreation marketing on the ecological safety of recreational areas of Crimea - H.V. Pashentseva (Marketing i Menedžment Innovacij, 2013)
The aim of the article. The purpose of the article is rationalization of use of the marketing resting place to ensure the ecological safety of recreational areas by reducing human pressure on them through differentiating of the recreants` flows.The results of the analysis. The essence of the formation period of anthropogenic load on Crimea recreational areas is identified and justified. There are three periods: the growth of human pressure, which is associated with the beginning of holiday season; the period of peak demand, which is due to mass holidays; pressure reducing caused by gradual finishing of holiday season.It was determined that the degree of dependence between anthropogenic pressure and ecological safety is high. It was found that for the period of peak demand random factors are 3,80%. Therefore the ecological safety of recreational areas in this period is the most sensitive to changes in recreants` flow.It was demonstrated the possibility of applying marketing recreation as a tool to ensure ecological safety of recreational areas, contributing to the reduction of anthropogenic pressure on them through the use of objective relationship price quality for tourism services.SWOT-analysis of the attractiveness of the Crimea recreational areas of the is represented: field SO (power opportunities), field of ST (strength threats), field of WO (weakness if possible), fieldofWT (capacity threats). Its results give opportunity led to rank these areas according to their attractiveness and to find the causes of ecological safety decline.Association between the level of prices for tourist services and the value of ecological security index (correlation coefficient 0,834-0,879) is demonstrated. The analysis of statistical data and the exponent of ecological safety revealed that a slight increase in the price of services within 1,18-1,46% contributes to the rise of ecological safety at 1,762,53%. In this case, a significant price increase in the range11,02-27,25% leads to a decrease of this index about 0,959,94%. This confirms the action of marginal pricetheory.Conclusions and directions of further researches. Using of the tools of place marketing can substantially improve the ecological situation of recreational areas by reducing the anthropogenic pressure of recreants. It becomes possible through applying the ratio of price quality to tourism services. Further studies consist in identifying the limits of price change for tourism services in Crimea region and determining of its effect on the level of ecological safety. It is necessary to develop economic and mathematical models, allowing predicting and defining the upper and lower limit of the price change, that do not result in economic losses.